2004
DOI: 10.1007/bf02980105
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the anti-inflammatory effects ofclerodendron trichotomum thunberg leaves

Abstract: Clerodendron trichotomum Thunberg Leaves (CTL) have been used for centuries in Chinese folk medicine for their anti-inflammatory properties. We have studied the anti-inflammatory effects of CTL extracts in rats, mice and in Raw 264.7 cells. 1 mg/kg solutions of the 30% and 60% methanol extracts of CTL were used and a 1 mg/kg of indomethacin was used as a positive anti-inflammatory standard; these were then administrated to rats. Carrageenan was injected subcutaneously to induce hind paw edema in rats. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In the present study, an active fraction, 80% methanol fraction and acteoside isolated active fraction have been demonstrated to possess both in vivo and in vitro anti-inflammatory effects, suggesting that acteoside is responsible for the anti-inflammatory activity of C. trichotomum. Choi et al (2004) and Park and Kim (2007) reported that the methanol extract of C. trichotomum leaves decreased edema induced by carrageenan, acetic acid-induced capillary permeability and lipopolysaccharide (LPS)-induced PGE 2 (Choi et al, 2004;Park and Kim, 2007). Using activity-guided fractionation, C. trichotomum methanol extract was chromatographed on a column of Diaion HP-20 (Nippon Rensui Co., Tokyo, Japan) and the anti-inflammatory effect of each fraction was determined using in vitro and in vivo assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, an active fraction, 80% methanol fraction and acteoside isolated active fraction have been demonstrated to possess both in vivo and in vitro anti-inflammatory effects, suggesting that acteoside is responsible for the anti-inflammatory activity of C. trichotomum. Choi et al (2004) and Park and Kim (2007) reported that the methanol extract of C. trichotomum leaves decreased edema induced by carrageenan, acetic acid-induced capillary permeability and lipopolysaccharide (LPS)-induced PGE 2 (Choi et al, 2004;Park and Kim, 2007). Using activity-guided fractionation, C. trichotomum methanol extract was chromatographed on a column of Diaion HP-20 (Nippon Rensui Co., Tokyo, Japan) and the anti-inflammatory effect of each fraction was determined using in vitro and in vivo assays.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al (2004) reported that a methanol extract of C. trichotomum exerted an anti-inflammatory effect by suppressing the production of prostaglandin E 2 (PGE 2 ). However, nothing is known yet about the anti-inflammatory components of C. trichotomum that mediate this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their antiparasitic property, some of these chemicals constituents could be responsible for the schistosomicidal effect of C. umbellatum leaves aqueous extract. Moreover, it has been found that some species of the genus Clerodendrum as C. petasites and C. trichotomum exhibited anti-inflammatory properties (Panthong et al, 2003;Choi et al, 2004). Given the fact that S. mansoni develops unique severe granulomatous inflammatory reactions in the liver, a plant extract with anti-inflammatory properties might be of great interest in the enhancement of the anti-inflammatory barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Clerodendron, is reported to demonstrate biological activities such as antitumorgenic [7,8] , Hypoglycemic, hypolipidemic [5,9] , Hepatoprotective activity against CCl 4 induced liver injury in rats [10,11] , Anti-inflammatory [12][13][14] , free radicalscavenging activity, Anti-diarrhoeal, Antinociceptive and antipyretic effects [15][16][17] . To the best of our knowledge, there is only one scientific report published regarding the phytomedicinal properties of CC by Adeneye et al [6] .…”
Section: Introductionmentioning
confidence: 99%